PENGUATAN MATERI BAHASA INDONESIA MELALUI IDENTIFIKASI KELAS KATA PADA SISWA KELAS VIII SMP NEGERI 3 AMBON - da Costa, Romilda Arivina; Hiariej, Chrissanty (Universitas Pattimura, 2025)
Language is not always oriented towards a regular structure. However, the quality of writing is greatly influenced by correct grammar because readers are helped to understand the right words, while avoiding misinterpretation. For this reason, a junior high school student who is surrounded by a number of writing assignments needs to have mechanical skills that are inseparable from knowledge and understanding of word classes. As a universal language element, word classes are owned by all languages, but the number and characteristics are different for each language. Sometimes junior high school students are often faced with foreign language structures so that the Indonesian language structure displayed in writing is often random and wrong. In order for this habit to be minimized, Reinforcement of Indonesian Language Material Through Identification of Word Classes for Class VIII Students of SMP Negeri 3 Ambon needs to be carried out. This PKM activity took place in presentation, discussion, and evaluation sessions. The results provide an overview that the common use of certain word classes in writing activities is often contrary to linguistic rules. To facilitate identification, a number of markers are presented as practical steps.